Geographical analysis of groundwater characteristics in Soran district - Khurshid, م. م. میدیا اسعد خورشید (Sulaimani Journal for Humanities, 2025)
Analyzing the types and characteristics of water in each region is important, but not only is the quantity of water resources in the region important, but the type of water, its physical and chemical properties, and its suitability for use in different fields are more important, and this is due to the specific standards for using water appropriate for each field. Therefore, this research is devoted to highlighting (a geographical analysis of the groundwater characteristics in Soran District). In this study, the deductive methodology and quantitative analysis through geographical information systems were used to treat and analyze the data. It also aims to clarify the spatial variation of this distribution in terms of water quality To achieve the main objective, I divided the research into two main sections. In the first section, we will get to know the study area and natural characteristics of the area. The second section consists of two requirements: the first requirement is the water resources in the study area, and the second requirement is an analysis of the chemical and physical characteristics of groundwater in the area. then the study presents several findings and recommendations, the most important of which are the use of Geographic Information System (GIS) helped identify water quality differences and create a scientific map of characteristics. The most obvious recommendations are to purchase control of private wells and streams by special legislation to prevent groundwater levels from decreasing and springs from drying up.
Keywords: Groundwater; GIS analysis (Geographic Information Systems); chemical and physical analysis